Developing support for mental health clinical research: the Mental Health Research Network experience. (May 2012) - Callaghan, Patrick; David, Anthony; Lewis, Shon; Marshall, Max; Szmukler, George; Wykes, Til; Ashcroft, Joanne; Burns, Stephanie
Research can improve people's health and well-being, and its use to guide the nation's health is written into UK NHS policy. The National Institute of Health Research supports research in the NHS through clinical research networks like the Mental Health Research Network (MHRN). The MHRN supports research working collaboratively with people using services and those providing them. It supports studies that are based within mental-health services, social-care services and within primary-care services, irrespective of methodological approach. The network helps researchers screen participants for eligibility, recruit participants, conduct assessments, collect data and liaise with clinicians to promote the value of research. The MHRN provides online resources about how to involve people using services and their families and friends in research, and on how services can support and engage with research. It also helps private companies recruit participants in the NHS.